Dynamic vs real time life cycle assessment - Antonia Vyrkou; Maria Aryblia; Nikolaos Savvakis; Ingrid Nicacio; Owais Siddique; George Arampatzis; Athanasios Angelis-Dimakis (Cleaner Environmental Systems, 2025)
The term “conventional” or “static” Life Cycle Assessment (LCA) is used to describe the traditional application of LCA for the environmental impact assessment of a given instance of a system, to differentiate it from the recently developed Dynamic Life Cycle Assessment (DLCA). The latter is defined as monitoring and assessing the environmental performance of a continuously changing system. However, the term “dynamic” has been interpreted differently in various studies, with the temporal aspect of the analysis being satisfied either with the use of timeseries of (historical/predicted) data or with a real-time data collection for the system in question. The focus of this review paper is: (a) to examine the implementation of DLCA by findings common themes, differences and challenges in its application to different sectors, and (b) identify and highlight the differences between dynamic assessment and real-time assessment.The review has shown that in the last five years the published literature has grown, with the annual number of articles increasing from less than 30 (between 2015 and 2019) to 62 in 2023. In terms of the traditional LCA steps, the Dynamic Process Inventory is usually populated eiterh (a) with historical data for certain elementary flows and/or (b) using alternative scenarios for selected elementary flows. Dynamic Characterisation is only needed when the time horizon is longer than a decade, while Dynamic Systems had been mostly implemented in correlation with the Building Information Model (BIM). The sectors where DLCA has been predominantly used are: (a) buildings; (b) waste treatment and management; (c) agriculture; and (d) utilities (i.e. energy production and water supply).On the contrary, the term “real-time LCA” is rarely used, with only a handful of published papers referring to it, but none of these implemented in a real-life industrial system. Although several studies agree that real-time assessment leads to improved accuracy, better insight to the process and time savings in the analysis, the effort required to implement it and the added value to the industrial plant, does not currently justify its wider implementation. However, in the era of Industry 4.0 and the digitization of industrial plants, there is an opportunity to incorporate the environmental impact assessment in the continuous monitoring of process industries.